Analysis of the Causes of Medical Records Document Misfiling at Makassar City Regional General Hospital - Andi Suhenda; Diana Barsasella; Ari Sukawan; Dedi Setiadi; Sugiharto Sugiharto; Prima Soultoni Akbar (Poltekkes Kemenkes Palu, 2025)
The procedure for storing medical record documents (MRDs) involves sorting the records by their medical record numbers before returning them to the medical records department and placing them in storage. This process facilitates the retrieval of required records and streamlines storage operations, thereby preventing misfiling when the documents are needed for patient care. Delays in locating MRDs on the filing racks can result from storage or placement errors, commonly referred to as misfiling. Efficient storage of medical record documents (MRDs) requires proper sorting by medical record numbers before returning them to the filing system. This process ensures quick retrieval and minimizes errors. However, delays in locating MRDs often occur due to misfiling—typically caused by improper storage or placement. This study aims to identify factors contributing to misfiling, focusing on the storage system, alignment, numbering, and human resources. This study is quantitative research with a descriptive design. The analysis used is univariant analysis. The population comprises inpatient medical records returned from the care units after patient discharge during the period of January to December 2023. The sampling method employed is non-probability sampling, specifically using accidental sampling. Among 50 inpatient MRDs stored in the filing room at Makassar City Regional General Hospital, 15 (30%) were misfiled. The factors contributing to the misfiling of medical record documents in the filing room include incompetent medical record personnel, misalignment in the filing system, the absence of tracers, and the lack of an expedition logbook. Misfiling was associated with several factors, including untrained personnel, inconsistencies in the filing alignment, absence of tracers, and the lack of a delivery logbook (previously referred to as an “expedition logbook”) used to track the movement of documents. Addressing these issues may improve filing accuracy and support patient care efficiency.